BIO-EKOLOGI TUMBUHAN OBAT KEDAWUNG (Parkia timoriana (DC) Merr.) DI HUTAN ALAM TAMAN NASIONAL MERU BETIRI (Bioecological of kedawung (Parkia timoriana (DC) Merr.) medicinal plant in natural forest Meru Betiri National Park) - Zuhud, Ervizal AM (Media Konservasi, 2011)
The article was describe some aspect of bioecological Parkia timoriana DC Merr in Meru Betiri National Park i.e. ecological characteristis, population dan regenration status, seed production, seed dispersal dan seed distributor, spatial distribution of parkia, and relation of parkia abundance and community interaction and distance of village to the forest (parkia habitat). In Meru Betiri National Park, tke parkia was found at 0 -500 m upper sea, topographyi 0-125 % (general 40 %), land pH 5 – 7. Total population of parkia in natural forest only 200 individu and naturally regeration process was very low. As a intolerant species, parkia was needed most sun radiation to sprout the seed and growth of parkia. The pattern of spatial distribution and abundance of parkia were relating to the interaction intensity of people to parkia and the distance of communities village to the parkia habitat in natural forest. In this case, the parkia abundance were found in natural forest where people who has highest interaction with parkia and nearest distance of communities village to the natural forest as parkia habitat. Peoples as parkia harvester was actor in parkia distribution and parkia seed dispersal in Meru Betiri National Park. Keywords : bioecological, kedawung, regeneration, conservation, community.